Development of Learning Media Assisted by Geogebra and Interactive Games on Cone Material - Muazarah, Salma Farihah; Qohar, Abd.; Sisworo, Sisworo (Unnes Journal of Mathematics Education, 2025)
The swift advancement of technology offers significant opportunities for the field of education. Technological progress serves as a tool to facilitate teaching and learning processes. One notable application is in the selection of learning media, which plays a crucial role in ensuring that educational activities align with current needs. The aim of this study is the researcher will develop learning media assisted by Geogebra and Interactive Games that are valid, practical, and effective on cone material. This study utilizes a research and development (R&D) approach, applying Thiagarajan’s 4-D model. The participants consisted of 26 students from class IX-B at the Laboratory Junior High School of Malang State University. The findings revealed that the media's validity scored an average of 80%, categorizing it as "Feasible," thus confirming its validity. Effectiveness was assessed by analyzing the test results of the 26 students, with an average score of 84, indicating strong effectiveness. Practicality was evaluated through a student feedback survey, which showed a practical rating of 80%. Based on these findings, the online interactive learning materials, utilizing GeoGebra and Construct 2 to create interactive games on cone volume, were deemed valid, practical, and effective, making them suitable for use in educational settings.